The Effectiveness of The Online Learning Medium Google Classroom on The Learning Outcome - Cornelia Susanty Maitimu; Jolanda Tomasouw; Patresia Silvana Apituley (Universitas Pattimura, 2021)
This research aims to describe the effectiveness of the online learning medium Google Classroom on the learning outcome of the subject German of the students at the XI-IPA 3 class SMA Negeri 3 Ambon. This research was carried out at the SMA Negeri 3 Ambon and the sample was twenty German learners from class XI-IPA 3 SMA Negeri 3 Ambon, academic year 2020/2021. This research has two variables, namely the learning media Google Classroom as a free variable and the learning outcome of the subject German as a bound variable. The method used in this research was experiment. The data of this research were determined through a questionnaire and learning outcome through a test (pre-test and post-test). The data from the questionnaires were processed with the Likert scale and then analyzed using the analysis technique “descriptive percentages of the questionnaires”. The data processing result showed that there was 71.62% in the “good” category. The learning results were then checked with the t-test and the result of the data processing showed that the value t calculation is greater than t table (t calculation: 16.96 ˃ 2.86 t table). That means that there is a difference between pre- and post-test in this result. The use of the learning medium Google Classroom is thus effective in helping German learners achieve better German learning results. Based on the result, it is suggested that this learning medium should use Google Classroom in German lessons